2012
DOI: 10.1016/j.neurobiolaging.2010.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Fractional anisotropy of water diffusion in cerebral white matter across the lifespan

Abstract: Determining the time of peak of cerebral maturation is vital for our understanding of when cerebral maturation ceases and the cerebral degeneration in healthy aging begins. We carefully mapped changes in fractional anisotropy (FA) of water diffusion for eleven major cerebral white matter tracts in a large group (831) of healthy human subjects aged 11-90. FA is a neuroimaging index of micro-structural white matter integrity, sensitive to age-related changes in cerebral myelin levels, measured using diffusion te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

39
315
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(359 citation statements)
references
References 70 publications
39
315
5
Order By: Relevance
“…We observed a substantial decrease in neurocognitive and DTI measures from young adulthood to old age, replicating several prior reports (6,37). Also, consistent with the literature, we found evidence for modest phenotypic correlations between neurocognitive and white-matter integrity, particularly for tests of speed of processing (27,38,39), working and declarative memory (12,13), and IQ (14,25).…”
Section: Discussionsupporting
confidence: 90%
“…We observed a substantial decrease in neurocognitive and DTI measures from young adulthood to old age, replicating several prior reports (6,37). Also, consistent with the literature, we found evidence for modest phenotypic correlations between neurocognitive and white-matter integrity, particularly for tests of speed of processing (27,38,39), working and declarative memory (12,13), and IQ (14,25).…”
Section: Discussionsupporting
confidence: 90%
“…The FA is a diffusion tensor imaging (DTI)-derived measure that is particularly useful as an estimate of the microstructure and specific organisation of myelinated axonal fibres, and may be considered an estimate of WM integrity (Basser & Pierpaoli, 1996). Using this measure, several authors (Hasan et al, 2007, Hasan et al, 2009Kochunov et al, 2012;McLaughlin et al, 2007) reported quadratic effects of age on FA values, with ages of peak between the third and fifth decades of life and a very slow decrease of FA values from these peaks to late senescence. Consequently, we can affirm that the quadratic relationship between age and oscillatory complexity shown by our results parallels the quadratic relationship between age and cortical WM.…”
Section: Discussionmentioning
confidence: 99%
“…The sequence parameters were: TE/ TR = 87/8000 ms, FOV = 200 mm, axial slice orientation with 50 slices and no gaps, five b = 0 images, and 64 isotropically distributed diffusion-weighted directions with b = 700 s/ mm2. These parameters maximized the contrast to noise ratio for FA measurements (Kochunov et al, 2012). A tractbased spatial statistics (TBSS) method was used for tractbased analysis of diffusion anisotropy (Smith et al, 2006).…”
Section: Diffusion Tensor Imagingmentioning
confidence: 99%